Methylphenidate Has Long-Lasting Metaplastic Effects in the Prefrontal Cortex of Adolescent Rats - Hernandez-Kunstmann, A; Burgos-Gallegos, H; Morales-Munoz, B; Cofre-Montenegro, C; Saez-Briones, P; Zeise-Ssa., M; Castillo-Borreda, A (Elsevier, 2015)
Methylphenidate (MPH) is widely used as a "nootropic" agent and in the treatment of disorders of attention, and has been shown to modulate synaptic plasticity in vitro. Here we present in vivo evidence that this MPH-induced metaplasticity can last long after the end of treatment. MPH (0, 0.2, 1 and 5. mg/kg) was administered daily to male rats from postnatal day 42 for 15 days. The animals were tested daily in a radial maze. Long-term potentiation (LTP), a marker of neural plasticity, was induced in vivo in the prefrontal cortex after 2-3. h, 15-18 days or 5 months without treatment. The behavioral performance of the 1. mg/kg group improved, while that of animals that had received 5. mg/kg deteriorated. In the 1 and 5. mg/kg groups LTP induced 2-3. h after the last MPH treatment was twice as large as in the controls. Further, 15-18 days after the last MPH administration, in groups receiving 1 and 5. mg/kg, LTP was about fourfold higher than in controls. However, 5 months later, LTP in the 1. mg/kg group was similar to controls and in the 5. mg/kg group LTP could not be induced at all. No significant changes of LTP were seen in the low-dose group of animals (0.2. mg/kg). Thus, firstly, doses of MPH that improve learning coincide approximately with those that augment LTP. Secondly, MPH-induced increases in LTP can last for several weeks, but these may disappear over longer periods or deteriorate at high doses. © 2015 Elsevier B.V.